Panelist Analysis of Higher Education Governance Instruments Based on Good University Governance Principles Using Many Facet Rasch Measurements - Iriyadi, Deni; Muhajir; Nikmatullah, Cecep; hartati, Hevriana (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2023)
This research aims to develop instruments related to measuring higher education governance so that it can fulfill the principles of good governance. This research used 3 panelists to measure the content validity of the instrument developed. The criteria for selecting experts/validators are adjusted to the expertise and needs of the instrument development being carried out. The study on testing the content validity of panelists uses Rasch Model analysis with the Facets application which aims to test subjectively rated statement items by looking at several aspects including unidimensional assumptions, testing model fit (item fit), and rater/expert consistency. The results of the content validity analysis carried out show that the unidimensional criteria (the raw variance explained by measure value is more than 20%), the item fit value (the outfit value is in the range of 0.5-1.5), and the rater consistency assessment show that all raters/experts meet the fitness criteria (outfit and infit value categories are in the range 0.5-1.5). The results of the content validity analysis carried out show that the quality of the instrument developed is suitable for use to measure higher education governance.